Teratogenic effects of Propylthiouracil on Swiss albino mice fetuses – A gross study - Tiwari, Samta; S K Pandey; Anand Mishra (Asian Journal of Medical Sciences, 2022)
Background: Propylthiouracil is an antithyroid drug used to treat hyperthyroidism in pregnancy, as euthyroid state is necessary for optimal pregnancy outcome. Few reports of fetal anomalies are associated with propylthiouracil use as compared to other antithyroid drugs, having severe teratogenic profile. Aims and Objectives: The present study has been conducted to divulge the teratogenic profile of propylthiouracil by observing its gross effects on mice fetuses, as limited data are available despite extensive usage of drug in pregnancy. Materials and Methods: A 100 mg/kg body weight/day of propylthiouracil was orally administered to pregnant Swiss albino mice on the 6th, 7th, and 8th days of gestation (treated group), while distilled water was given orally to pregnant dams of the control group (same volume and for same duration). The fetuses were collected, weighed, and studied for gross abnormalities after sacrificing the pregnant dams on the 18th day of conception. Results: In the present study, the treated group shows reduction in various growth parameters (mean body weight, mean crown-rump length, etc.) depicting growth retardation, in comparison to the control group. On examination, engorged cutaneous vessels, external hemorrhage, and omphalocele were also observed in the treated group. Conclusion: As propylthiouracil is observed to have teratogenic outcome, hyperthyroidism during the first trimester must be treated with minimum effective dose of the drug.